Fat Delta 2: functorial subgroups of topological abelian groups - Dikranjan, Dikran; Lewis, Wayne; Loth, Peter; Mader, Adolf (Topology Proceedings, 2022)
In the predecessor [16] of this paper the canonical subgroup (Fat Delta) Δ(G) of a compact abelian group G was studied. It is the sum of all closed disconnected subgroups of G and it appeared before in the literature (see [28]) as td(G), defined for arbitrary topological groups and motivated by completely different considerations. We introduce and compare further functorial subgroups of general topological groups and study their relationships with Δ(G) and td(G).